Podejścia do ustalania skal pomiaru w międzynarodowych analizach przestrzennych - Sobczak, Elżbieta (Approach for Setting Measurement Scales in International Spatial Analyses, 2005)
The objective of this study is the characteristics and evaluation of possible approaches to the development of measurement scales useful in international spatial analyses. Criteria of measurement scales evaluation and difficulties connected with their construction in a multicultural environment were discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (3); 2005; nr 1075, s. 217-223